ON SOME FORMULAS FOR THE INDEX OF LINEAR BOUNDED OPERATOR - Khachatryan, I. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
We consider the linear bounded operator in infinite dimensional separable Hilbert space satisfying some conditions. We prove formulas that can be used to calculate the index of this operator.
Keywords: operator; ndex; trace; absolute norm